Persepsi Konsumen Tentang Strategi Konten Promosi Iklan Flash Sale 12.12 Shopee - Mayang Riyantie; Alamsyah Alamsyah; Misnan Misnan (Prisani Cendekia Institute, 2022)
Flash Sale is one of the most effective types of advertising content strategies in communicating products and services, because flash sales are able to provide promotional messages with high appeal. This is in accordance with the desire and satisfaction of consumerism. This study aims to determine the response of shopee users regarding the promotional content of